Reconfiguring the RUFORUM E-Learning Platform for Improved Climate-Smart Online Learning Access and Delivery - Chinpuza, Unity; Nakayiwa, Florence Mayega; Majaliwa, Jackson Gilbert Mwanjalolo (2025)
RUFORUM and WASCAL developed climate-smart agriculture and climate information services modules and uploaded them to the RUFORUM Moodle platform to broaden access. A review showed major technical and usability problems, making an upgrade necessary. RUFORUM, through AICCRA, therefore redesigned thirteen courses and modernised the platform using stronger authoring tools (Articulate Rise 360, iSpring Cloud, Adobe Captivate). A phased approach guided the process, replacing outdated eXe-based content and improving interactivity, compatibility, and overall learning experience.